1 `-Methyl-2-oxo-5 `-phenylspiro[indoline-3,3 `-pyrrolidine]-4 `,4 `-dicarbonitrile - Nabid, M.R.; Rezaei, S.J.T.; Fazaeli, Y.; Ng, S.W. (International Union of Crystallography, 2010)
The title spiro-compound, C(20)H(16)N(4)O, crystallizes with four independent molecules in the asymmetric unit. In all of them, the oxindole unit is planar, the r.m.s. deviations ranging from 0.07 to 0.08 angstrom, while the pyrrolinyl ring adopts an envelope conformation (with the N atom representing the flap). In the crystal, adjacent molecules are linked by N-H center dot center dot center dot N and N-H center dot center dot center dot O hydrogen bonds.